2007
DOI: 10.1016/j.joca.2006.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of serum cytokines in the Hartley guinea pig model of osteoarthritis

Abstract: Only the age and weight-independent associations of IL-6 and G-CSF with histological OA were significant under the conditions imposed by the Holm step-down adjustment for multiple comparisons. Though the observed changes of these cytokine levels may be due to a correlation with age, it is highly unlikely given the significant difference between Hartley and Strain 13 age-matched cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
4
16
0
Order By: Relevance
“…It has been con rmed that the levels of pro-in ammatory cytokines, such as TNF-and IL-1b, increase sharply during the early stages of OA progression. Animal and in vitro studies have con rmed that the in ammatory cytokine TNF-can induce bone resorption and enhance cartilage degradation in OA [41,42]. In our study, we found higher immunohistochemical and mRNA expression of TNF-, which can stimulate the production of other cytokines, such as IL-6, prostaglandin, and MMP [41] as well as decrease type II collagen and proteoglycan levels [43].…”
Section: Discussionsupporting
confidence: 63%
“…It has been con rmed that the levels of pro-in ammatory cytokines, such as TNF-and IL-1b, increase sharply during the early stages of OA progression. Animal and in vitro studies have con rmed that the in ammatory cytokine TNF-can induce bone resorption and enhance cartilage degradation in OA [41,42]. In our study, we found higher immunohistochemical and mRNA expression of TNF-, which can stimulate the production of other cytokines, such as IL-6, prostaglandin, and MMP [41] as well as decrease type II collagen and proteoglycan levels [43].…”
Section: Discussionsupporting
confidence: 63%
“… 45 , 46 In Hartley guinea pig model of OA, IL-6 levels in serum were positively correlated with histological score of OA, which was independent of age or weight. 47 Another report by Tonchera et al 48 concluded that serum levels of IL-6 were significantly higher in patients with active OA compared with healthy subjects. Furthermore, there is a direct correlation in IL-6 expression level and clinical outcome of rheumatoid arthritis, and blocking of IL-6 function has emerged a new therapeutic strategy for RA and related inflammatory disease.…”
Section: Discussionmentioning
confidence: 97%
“…48 Significant positive correlations were found between the SDF-1, GAG, and C2C synovial fluid concentrations and the Mankin score. Huebner et al 46,49 showed that the Hartley strain exemplified a serum/chemokine profile indicative of a pro-inflammatory state compared with Strain 13. Among the cytokines and chemokines elevated in the Hartley strain, they found IL-6, IL-17, IL-8, and TNF-α.…”
Section: Guinea Pigsmentioning
confidence: 99%